Correlation of Malocclusion, Dental Crowding With Dental Caries and Calculus in Mixed Dentition : Korelasi Antara Maloklusi dan Gigi Berdesakan dengan Karies Gigi dan Karang Gigi pada Masa Pertumbuhan Gigi Campuran - Lila Muntadir; Twi Agnita Cevanti; Lambang Bargowo; Nining Dwi Suti Ismawati; Windy Yuliartanti; Wanda Karisma Dian Sari; Rizqi Aulia Kusuma Andini; Marisa Elvi Dayanti; Eka Setyawardana; Reni Puspa Daniati (Academia Open, 2026)
General Background: Mixed dentition is a transitional stage characterized by dynamic occlusal development, while irregular tooth alignment may create plaque-retentive areas that complicate oral hygiene. Specific Background: Although crowding may facilitate biofilm retention, evidence linking this condition with caries during mixed dentition remains inconsistent. Knowledge Gap: Available evidence regarding crowding as a caries-related factor is limited and heterogeneous, particularly when caries experience in permanent and primary teeth is assessed separately. Aims: This cross-sectional study examined the relationship between crowding and caries status, DMFT, and deft among 30 fourth-grade students aged 10–11 years. Results: Crowding occurred in 83.3% of participants and caries in 60.0%. Fisher’s exact test showed no significant relationship between crowding and caries status (p = 0.066). DMFT did not differ significantly between groups (U = 75.50; p = 0.439), and deft likewise showed no significant difference (U = 85.00; p = 0.171). Novelty: The study provides sample-specific evidence by evaluating crowding against caries status while separately examining permanent and primary tooth caries indices during mixed dentition. Implications: Crowding alone does not sufficiently explain caries experience in this sample. Interpretation requires caution because of the small and imbalanced groups, incomplete crowding-severity data, and cross-sectional design. Highlights: Alignment irregularity was recorded in 83.3% of the sample. Fisher’s exact testing remained above the significance threshold (p = 0.066). DMFT and deft comparisons were nonsignificant (p = 0.439 and p = 0.171). Keywords: Dental Crowding, Dental Caries, Mixed Dentition, DMFT, Deft